Implementasi Program Ibadah Seksi Pelayanan Remaja dan Pemuda (SPRP) Jemaat GKE Barimba dalam Pembinaan Karakter - Ophilia Lindy Agrecia; Siren Nugroho; Cintya Fioni; Prita Aura Eklesia (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Implementation of the Youth and Youth Service Section (SPRP) Worship Program at the GKE Barimba Congregation in the context of developing the character of Christian teenagers and young people. Using descriptive qualitative methods, data was collected through in-depth interviews with youth and youth leaders who play an active role in development activities at the church. The results of the study revealed various challenges faced by teenagers and young people, such as peer pressure that affects worship motivation, a less engaging atmosphere of togetherness in worship, and differences in age and maturity levels between teenagers and young people that cause emotional distance. Their spiritual needs include relational aspects, a contextual understanding of faith, real spiritual experiences, and the formation of strong moral character to face the challenges of the modern era. Effective development strategies involve the active role of families in spiritual development at home, Christian educators as guides and motivators, the use of interactive learning methods such as Bible-based games and digital media that are relevant to the character of the younger generation, and the implementation of dynamic and creative worship services to increase engagement. The implementation of this program aims to form a strong Christian character and prepare teenagers and young people to become faithful, responsible individuals who are able to serve actively in the church and society. Close synergy between family, church, and education is a key factor in the success of spiritual development of the younger generation amidst rapid social and technological change.